Fracture behavior of self-compacting semi-lightweight concrete containing nano-silica. Issue 10 (July 2019) - Afzali-Naniz, Oveys; Mazloom, Moosa
This study investigates the effects of colloidal nano-silica content on the fracture parameters and brittleness of self-compacting semi-lightweight concrete. For this purpose, eight mix compositions were prepared with various contents of colloidal nano-silica (0%, 1%, 3%, and 5%) and two water to binder ratios of 0.35 and 0.45. A total of 96 notched beams of different sizes were made and three-point bending tests were conducted on them. The fracture parameters of all semi-lightweight concrete mixes were specified and analyzed by size effect method. The results of this research indicated that using colloidal nano-silica in semi-lightweight concrete and decreasing water to binder ratio from 0.45 to 0.35, (1) fracture energy ( Gf ) and fracture toughness ( KIC ) of semi-lightweight concrete increased, (2) the brittleness number of semi-lightweight concrete increased, (3) the best effects of colloidal nano-silica on the mechanical properties and the fracture parameters of semi-lightweight concrete were obtained when cement was replaced by 3% of colloidal nano-silica, and (4) failure behavior of the semi-lightweight concrete moved to the strength criterion.